Istisna` risk Management in Islamic Banks - SOLTANI, Hachemi; SEFFIH ,Sadek (Finance and Business Economies Review, 2022)
This study aimed to identify the policies and procedures applied in Islamic banks to manage the risks of the Istisna` model. To achieve this objective, a descriptive and a case study approach were applied to identify the risks that can arise from implementing this model, and the adequate plans to face them. The study found that the Islamic bank faces many risks, when applying the Istisna` model, and by studying the case of Malaysia, it became clear that the country relies on several policies and procedures, such as using takaful insurance, guarantees, and adhering to the decisions and guidelines of the Basel Committee (BCBS) and Islamic Financial Services Board (IFSB).